Tyrosinase Electrochemical Biosensors Monitoring Medicinally Significant Substances - Sýs, Milan; Vytřas, Karel (Current Medicinal Chemistry, 2018)
Nowadays in biosensing, development of analytical techniques is focused on improvement for monitoring biologically active species in living organisms, especially in real-time analysis. This article provides an overview of applications of electrochemical tyrosinase biosensors in the analysis of medicinally significant substances, also known as biomarkers. At the beginning, special attention is paid to characterisation of the tyrosinase enzyme, explanation of reaction mechanisms of tyrosinase with various types of electrochemical transducers and techniques needed for stable immobilization of this biocatalyst on the transducer surface used. In this case, amperometric transducers represent the most frequently used type of electrochemical sensing because they usually provide sensitive current response to the presence of analyte in the sample. Many scientific works suggest that these very selective bioanalytical devices could find application in the clinical diagnosis of various serious diseases because they represent the effective analytical tools for diagnosis of neurodegenerative disorders, detection of microbial pathogens responsible for foodborne illness and diagnosis of cytopathology, especially melanoma cancer. Additionally, various kinds of electrochemical tyrosinase biosensors are presented which were developed to determine the catalytic activity of other enzymes significant for human metabolism, medicaments and their metabolic products, several hormones, amino acids and proteins. Despite all of their advantages, it is necessary to state that tyrosinase biosensors are still not used in the routine laboratory practice due to their relatively short service life which is not longer than one month unfortunately. Never-ending development of catalytic polymers imitating the tyrosinase active site could be one of ways to solve this serious drawback.
Keywords: diagnosis